Analisis Komoditas Basis Hortikultura dan Proyeksi Produksi Di Kabupaten Tabalong - Ahmad Suhaimi; Naparin Naparin (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2017)
This study aims to determine the commodity base of horticulture in Tabalong Regency and analyze production projections and forecast production in the next 5 years. The method used in analyzing the data available from related institutions in the government of Tabalong Kabuptaen is the Location Qoutient (LQ) Analysis method and the Trend Analysis method. Determining sub-district base commodities is done by Analysis of Location Qout (LQ) from 12 Subdistricts in Tabalong Regency there are 5 Subdistricts whose LQ values are above 1. Forecasting horticulture production in the next 5 years is done by Trend Analysis based on the results of analysis of 5 sub-districts the amount of production in 2017 for large chili commodities is 18.4% forecasting in 2021 amounting to 21.6% and for tomat plants commodities in 2017 the number of production is 17.7% forecasting in 2021 is 22.3% this figure indicates an increase in the number large production.